Multibeam bathymetry processed data (Atlas Hydrosweep DS 3 echo sounder entire dataset) of RV POLARSTERN during cruise PS142, Atlantic Ocean - Dreutter, Simon; Lemire, Annie; Dorschel, Boris (PANGAEA, 2024)
Multibeam data were collected during RV Polarstern cruise PS142 (2024-04-16 to 2024-05-13). Multibeam sonar system was Atlas Hydrographic Hydrosweep DS 3 multibeam echo sounder. Data are processed with Caris HIPS, including sound velocity correction with SV data from CTDs and World Ocean Atlas 18 (https://www.ncei.noaa.gov/archive/accession/NCEI-WOA18), tidal correction with TPXO9_atlas_v5 (https://www.tpxo.net/global/tpxo9-atlas), and manual cleaning. The soundings are combined in daily files, the format is XYZ ASCII (<Lon> <Lat> <Depth in meters, positive up, relative to mean sea level>). Additional blockmedian grids have been computed with depth dependent cell size to visualize the data. These grids are not meant for scientific analysis or navigation, but for overview purposes only.
Keywords: Atlantic Ocean; Bathymetry; Hydrosweep DS3; Multibeam; Polarstern